The Effect of Continuous Neuromuscular Blockade in a Cohort of Patients with Evolving or Grade 3 Bronchopulmonary Dysplasia - Cosnahan, Anna; Farraj, Farida A.; Mitchell, Joanna; Bauer, Sarah E.; Conlon, Steven; Rose, Rebecca (American Journal of Perinatology, 2025)
This study aimed to describe the use of continuous neuromuscular blockade (NMBA) in patients with life-threatening hypoxia and/or hypercarbia secondary to evolving or grade 3 bronchopulmonary dysplasia (BPD) and its association with short-term death, as well as clinical measures of respiratory severity.We identified a cohort of patients with evolving or grade 3 BPD at Riley Children's Health who received continuous infusion vecuronium for greater than 48 hours. We analyzed data using descriptive and inferential statistics.Of the 18 patients identified, 77% survived beyond 7 days after discontinuation of a single course of continuous vecuronium. All but one patient demonstrated decreased respiratory severity score (RSS) and oxygenation saturation index (OSI) across the period of NMBA administration. Mean RSS and OSI decreased significantly across the time of administration (p = 0.003) and was higher in the group that died versus the group that survived (p < 0.001, p = 0.001). Of those that survived to discharge, six received a tracheostomy, and one was discharged in room air.A majority of a cohort of patients with life threatening hypoxia and/or hypercarbia and evolving or grade 3 BPD exposed to continuous NMBA demonstrated a clinically significant incidence of short-term survival and reduced respiratory severity.
Keywords: bronchopulmonary dysplasia; neuromuscular blockade; premature; infant